An investigation of the learning processes that take place during practical work activities when using electrical circuit boards in grade: a case study - Accom, Gerald Charles (Rhodes University, Faculty of Education, Department of Education, 2012)
Since the introduction of Outcomes Based Education (OBE) as a preferred method of teaching and learning with Curriculum 2005 in 1997, its existence has come under continuous threat for the past thirteen years. Its teething experiences included a revision in 2004 which saw the introduction of the Revised National Curriculum Statements (RNCS) and most recently, we are now standing on the threshold of the implementation of the Curriculum Assessment Policy Statements (CAPS) in 2012. Throughout the turbulent educational milieu, social constructivism has always been upheld as the preferred teaching and learning methodology and millions of rands have been invested in this regard. This study is thus premised on the concern that now after all the years of actively promoting social constructivist methodologies, the implementation of the CAPS could seriously negate reasonable strides made in this regard. Triggered by these curricular issues, a qualitative case study was conducted at a school in Grahamstown in the Eastern Cape, South Africa, investigating the learning processes occurring in group work sessions during lessons involving practical work in electricity using circuit boards in grade 8. Underpinned by an interpretivist paradigm, the study took place in two phases. The data was mainly generated through audio and video recording of two focus groups. An open coding system was employed to derive analytical categories and frequency tables were used to establish trends. In order to validate the data, two observer teachers were involved throughout the research process and this was followed up with semistructured interviews after the second phase. The two case studies, involving learners fitting a similar profile in respect of mother-tongue and age group, were engaged in a similar activity for almost a year apart. This study anticipated the revelation of the extent to which group practical activities in electricity promoted learning, how knowledge is constructed in group-settings and whether practical activities involving electrical circuit boards in grade 8 enhance learning? The main findings of my study revealed that these practical activities can promote learning and therefore should remain a preferred method of teaching.
Keywords: Competency-based education -- South Africa -- Eastern Cape -- Case studies; Educational tests and measurements -- South Africa -- Eastern Cape -- Case studies; Education -- Evaluation -- South Africa -- Eastern Cape -- Case studies